Studies on the effects of microclimates on the distribution of larval ticks in the Eastern Cape Province - Kraft, Mary Kay (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1962)
1. In studying the effects of micro-climates on the distribution of larval ticks in the Eastern Cape Province four species were considered, namely, Boophilus decoloratus (Koch), Rhipicephalus evertsi (Neu), Amblyomma hebraeum (Koch) and Ixodes pilosus (Koch). 2. Three types of investigation were made:- i) autumn and spring surveys of the distribution of larval clusters, which were assumed to be close to positions in which egg-masses had been laid. - (Four species); ii) observations on the survival and development of eggs and engorged female ticks in microclimatically distinct field plots. - (Four species); iii) observations on the behaviour of the larvae and of the engorged female ticks. - (B. decoloratus). 3. The survey and plot data suggest that in autumn larval clusters of I. pilosus were to be found only in well-shaded situations because more exposed places were micro-climatically unfavourable to the survival of earlier stages. 4. The surveys show that in spring 1957 larval clusters of I. pilosus were to be found in unshaded, as well as in shaded, situations. 5. The survey and plot data indicate that the winter of 1957 was not favourable to the development of larvae of B. decoloratus, and that in spring new larval clusters may be expected to appear first in the warmest situations and later in the generally cooler places. 6. The plot data show that during hot and dry periods exposed situations were unfavourable to tho engorged females and eggs of all four species considered, but that during such periods these stages could sometimes survive in well-shaded places. 7. The survey and plot data show that in autumn and in spring larval clusters of B. decoloratus and R. evertsi may be present in unshaded situations. 8. The plot investigations provide little information about the distribution of larval clusters of A. hebraeum, but the survey data suggest that it is not remarkably different from that of B. decaloratus and R. evertsi. 9. There is a discrepancy in the survey and plot data: the surveys show that larval clusters of R. evertsi, and B. decoloratus were rare or absent from well-shaded situations, whereas tho plot data suggest such situations were micro-climatically favourable to larval developmcnt during the months preceding Autumn. 10. The observations on the behaviour of larvae and engorged females of B. decoloratus provide information which suggests that the behaviour of those stages may account for the rarity of larval clusters in well-shaded places. 11. The relative density of larval clusters of B. decoloratus is evidently also affected by factors other than micro-climate . The dropping- off behaviour of engorged female ticks appears to be possibly important in this.
Keywords: Ticks -- South Africa -- Eastern Cape; Ticks -- Ecology -- South Africa -- Eastern Cape; Ticks -- South Africa -- Eastern Cape -- Geographical distribution; Ticks -- Control -- South Africa -- Eastern Cape; Ixodidae -- South Africa -- Eastern Cape; Microclimatology -- Research -- South Africa -- Eastern Cape